Design, manufacturing and testing of a rotorcraft access panel door from recycled carbon fiber reinforced polyphenylenesulfide - Bruijn, T. A. de (2019)
An integrally-stiffened access panel for a rotorcraft is selected for detail design, testing and actual flight to demonstrate a novel recycling route for thermoplastic composites. The design, development and validation followed the ‘Building Block approach’. The used material is post-industrial carbon fiber reinforced polyphenylene sulfide waste. This material originates from thermoplastic components of the very same rotorcraft as the panel will be mounted on, improving traceability, logistics and fixing supply and demand. Material data have been gathered from mechanical tests and used to predict the panels strength and stiffness. A critical design detail was selected and tested for validation. This section was included in a manufacturing demo, along with other integrated design features, enabling testing the processability. The final panel design was successfully produced and tested on component level. The re-manufacturing process includes simultaneously applied heat and low-shear mixing, followed by compression molding in an isothermal mold. This offers the possibility to retain long fibers and therefore high mechanical properties at short cycle times. In comparison to the current carbon/epoxy solution, the resulting product is lighter, significantly more cost-effective and made of recycled material (fiber and matrix). The prototype panel is targeted for flight testing on the rotorcraft in 2019.